A Bayesian method for characterizing population heterogeneity - Dale O. Stahl (Games, 2019)
A stylized fact from laboratory experiments is that there is much heterogeneity in human behavior. We present and demonstrate a computationally practical non-parametric Bayesian method for characterizing this heterogeneity. In addition, we define the concept of behaviorally distinguishable parameter vectors, and use the Bayesian posterior to say what proportion of the population lies in meaningful regions. These methods are then demonstrated using laboratory data on lottery choices and the rank-dependent expected utility model. In contrast to other analyses, we find that 79% of the subject population is not behaviorally distinguishable from the ordinary expected utility model.
Keywords: C11; C12; D81; 330; Bayesian methods; behavioral distinguishability; identifying types; population heterogeneity; rank-dependent expected utility